Transnational patterns, social networks and self-help organizations for migrant women [version 2; peer review: 1 approved, 2 approved with reservations] - Paolo Ruspini; Petko Hristov (Open Research Europe)
Previous research shows the importance of building up self-help structures in a transnational perspective for the inclusion of migrant women who are fleeing their home countries because of war, violence, or different forms of vulnerability. The mobilization of self-help organizations through the intersection of transnationalism and gender is, in fact, a useful direction for a practice-oriented pedagogy directed both towards (1) the most vulnerable groups of women, or (2) those already empowered either as community leaders or network facilitators, other migrants and the whole native population. For this paper, we compare two video-interviews of refugee women collected in Bulgaria and Italy, which are important receiving countries either at the South-Eastern or Southern external border of the European Union. The research questions of this comparative assessment include: 1) How do refugee women organize themselves for mutual help? 2) How do they build their social networks through transnational practices to bridge with the local people? 3) Is community or individual empowerment of refugee women better for implementation through ethnic lines or a gender perspective? The final aim of this investigation is to analyse various patterns of social networks’ creation among refugee women originating from different socio-cultural contexts. The research findings might be useful to instil inclusion practices which are apt to refugee women empowerment.